1990
DOI: 10.1104/pp.92.4.970
|View full text |Cite
|
Sign up to set email alerts
|

Induction of an Extracellular Ribonuclease in Cultured Tomato Cells upon Phosphate Starvation

Abstract: Suspension-cultured cells of tomato (Lycopersicon esculentum) start to secrete an RNA-degrading enzyme activity during transition from logarithmic to stationary growth phase. Using affinity chromatography on agarose-5-(4-aminophenyl-phosphoryl) uridine 3'(2') monophosphate as a powerful and final enrichment step, the enzyme was purified to homogeneity and characterized as ribonuclease I (RNase I) according to the following data: (a) it has an Mr of 22,000 (sodium dodecyl sulfatepolyacrylamide gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 29 publications
1
86
0
2
Order By: Relevance
“…Biochemical adaptations to Pi starvation include increased synthesis of anthocyanins, presumably to adjust photosynthetic light reactions to the Pi-dependent Calvin cycle, and increased synthesis of enzymes for scavenging intra-and extracellular phosphorus (Trull et al, 1997;Bosse and Kö ck, 1998;Raghothama, 1999). We previously demonstrated that Pi starvation coordinately induces ribonuclease, phosphodiesterase, and acid phosphatase activities in tomato (Lycopersicon esculentum) cell suspension cultures, which sequentially participate in the complete hydrolysis of exogenous RNA to nucleosides and Pi (Nü rnberger et al, 1990;Abel et al, 2000). Here, we found that Phi effectively prevents accumulation of anthocyanins and represses these nucleolytic enzymes in Pi limiting conditions at concentrations that are not growth inhibitory.…”
Section: Table II Repression Of Pi Starvation-inducible Enzymes By Pmentioning
confidence: 99%
“…Biochemical adaptations to Pi starvation include increased synthesis of anthocyanins, presumably to adjust photosynthetic light reactions to the Pi-dependent Calvin cycle, and increased synthesis of enzymes for scavenging intra-and extracellular phosphorus (Trull et al, 1997;Bosse and Kö ck, 1998;Raghothama, 1999). We previously demonstrated that Pi starvation coordinately induces ribonuclease, phosphodiesterase, and acid phosphatase activities in tomato (Lycopersicon esculentum) cell suspension cultures, which sequentially participate in the complete hydrolysis of exogenous RNA to nucleosides and Pi (Nü rnberger et al, 1990;Abel et al, 2000). Here, we found that Phi effectively prevents accumulation of anthocyanins and represses these nucleolytic enzymes in Pi limiting conditions at concentrations that are not growth inhibitory.…”
Section: Table II Repression Of Pi Starvation-inducible Enzymes By Pmentioning
confidence: 99%
“…Confirmation that SAP1 and SAP2 are their genuine physiological substrates awaits the purification and kinetic characterization of both proteases. It will also be of interest to assess whether extracellular Pi-inducible proteases degrade additional hydrolytic enzymes that are specifically secreted into the CCF by )Pi tomato cell cultures, namely PSI ribonucleases and phosphodiesterases [2,14,20,21]. Although the functional importance of Pi-inducible secreted proteases in response to Pi-sensing and turnover of extracellular PSI proteins remains to be determined, the current study presents the first evidence for protease upregulation in response to Pi-resupply of )Pi plants.…”
Section: Discussionmentioning
confidence: 96%
“…SDS-PAGE analyses have revealed that the CCF of +Pi, )Pi, and Pi-resupplied tomato suspension cells contain up to 50 different polypeptides, several of which are unique to )Pi cultures [20,24] (also this study, not shown). This suggests that the pair of Pi-inducible secreted serine protease isoforms of cultured tomato cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12). Nürnberger et al (1990) and Löffler et al (1992) showed that both extracellular and intracellular RNase activities were induced in tomato-cell culture under P deficiency. Extracellular RNase could help degrade the RNA from senescing cells that have been either damaged or lysed, and also help degrade any RNA that might be present in the rhizosphere.…”
Section: Lipid Composition and Phenolics Concentration In Root-tip Pomentioning
confidence: 99%